Right vertical axillary incision vs. median sternotomy for congenital ventricular septal defect repair in children: a propensity score-matched study - Liu, Lijuan; Wang, Chenhan; Dong, Jie; Lin, Jiayi; Liu, Mingxiao; Li, Wei; Zeng, Debin; Yang, Xiaohui; Deng, Xicheng (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo retrospectively assess the outcomes of open-heart repair for ventricular septal defect in children using a right vertical axillary incision compared to median sternotomy.MethodFrom January 2022 to May 2023, children who underwent open-heart surgery for the repair of congenital ventricular septal defect in our department were selected for a propensity score-matched study. The propensity score matching method was utilized to pair children in the right vertical axillary incision group with those undergoing surgery via median sternotomy at a 1:1 ratio, based on age and weight.ResultsThere were 35 cases in each group. In the right vertical axillary incision group, the median age was 15 (7–40) months and the median weight was 8 (7–12) kg. In the median sternotomy group, the median age was 7 (3–37) months and the median weight was 7 (5–14) kg. The age (Z = −1.871, p = 0.061) and weight (Z = −1.462, p = 0.144) of the two groups showed no significant differences. The right vertical axillary incision group exhibited a significantly shorter incision length compared to the median sternotomy group (p < 0.001). Additionally, the median postoperative drainage was lower in the right vertical axillary incision group than in the median sternotomy group (p = 0.044), indicating statistical significance. No significant differences were observed between the groups concerning operation time (p = 0.565), bypass time (p = 0.855), cross-clamp time (p = 0.204), oxygenation index one hour post-surgery (p = 0.651), pleural effusion at 12 h post-surgery (p = 0.470), abnormal postoperative electrocardiogram (p = 0.452), cardiac intensive care unit duration (p = 0.211), or length of hospital stay (p = 0.095). The hospitalized children were followed up for 3 months to 1 year, during which there were no fatalities or complications.ConclusionOpen-heart repair of congenital ventricular septal defect through a right vertical axillary incision is a safe and effective surgical technique that minimizes surgical trauma and enhances aesthetic outcomes.